Cross-sectional assessment of infants' exposure to toxic metals through breast milk in a prospective cohort study of mining communities in Ghana - David Kwaku Bansa; Adolf Kofi Awua; Rose Boatin; Theodosia Adom; Edward Christian Brown-Appiah; Kennedy Kwame Amewosina; Akusika Diaba; Dominic Datoghe; Wilhelmina Okwabi (BMC, 2017)
Abstract Background Although breastfeeding of infants is recommended globally, the fact that maternal toxic metal stores are mobilised into breast milk implies infants, whose mothers live and work in mining communities, are at risk of multiple exposure to mining related toxic metals, such as Lead (Pb), Mercury (Hg), Cadmium (Cd) and Arsenic (As), through breast milk intake, in addition to in utero exposure. Method A total of 114 mother-baby pairs, recruited from two community hospitals servicing mining communities in two different regions in Ghana (57 each), were involved in this study. When the babies were 3 months old, the amount of breast milk intake, concentrations of selected toxic metals in the breast milk and therefore the amount of toxic metals exposure through breast milk were determined. The study also, determined the amount of these toxic metals in the hair and urine of each mother-baby pair at 3 months postpartum. Results Based on the amounts of milk intake and non-milk oral intakes (geometric mean of 0.701 (95% CL 0.59-0.81) Kg/day and median of 0.22 Kg/day respectively), 90% of the babies were determined to have been exclusively breastfed. The amounts of most of the toxic metals in breast milk were higher than the WHO set limits and for 46.4%, 33.3% and 4.4% of the babies, their intake of As, Hg and Pb respectively were above the WHO provisional tolerable daily intake (PTDI) values. Conclusion An appreciable proportion of babies living within the communities served by the Mangoasi Community Hospital in the Obuasi Municipality of the Ashanti Region and the Dompime Health Centre in the Tarkwa Municipality of the Western Region were exposed to Hg, As and Pb through breast milk in excess of what they should and these may have health implication for the infants and therefore calls for interventions.